EMS discipline: did it contribute to inflation convergence? - BINI SMAGHI, L. (PSL Quarterly Review, 2013)
The paper focuses on the cross-section comparison of inflation performance inside and outside the EMS. The evidence contained in the literature is first reviews. The author then examines some of the limitations of the analysis contained in the literature and presents new empirical evidence that takes into account some aspects that were previously ignored. JEL Codes: E31, E52, F15